State aid to state owned enterprises in South Africa : the need for a comprehensive State aid policy : a competition law inquiry - Afrika, Sasha-Lee Stephanie (Stellenbosch : Stellenbosch University, 2020)
Thesis (LLD)--Stellenbosch University, 2020.